2004
DOI: 10.1007/s10038-004-0197-5
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of phenylketonuria in Koreans

Abstract: Phenylketonuria (PKU) is an inborn error of metabolism that results from a deficiency of phenylalanine hydroxylase (PAH). We characterized the PAH mutations of 79 independent Korean patients with PKU or hyperphenylalaninemia. PAH nucleotide sequence analysis revealed 39 different mutations, including ten novel mutations. The novel mutations consisted of nine missense mutations (P69S, G103S, N207D, T278S, P281A, L293M, G332V, S391I, and A447P) and a novel splice site variant (IVS10À3C>G). R243Q, IVS4À1G>A, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
47
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 13 publications
10
47
0
1
Order By: Relevance
“…The p.R408W mutation was the predominant mutation in Ireland, Latvia and Lithuania (O'Donnell et al 2002;Kasnauskiene et al 2003;Pronina et al 2003), whereas c.1315+1G>A had the highest frequency in England, Germany and Denmark (Guldberg et al 1993;Aulehla-Scholz and Heilbronner 2003;Zschocke 2003). Other examples of region-specific mutations include c.1066-11G>A from Mediterranean regions and p.R243Q and p.R413P from Asia (Chien et al 2004;Lee et al 2004;Song et al 2005). The low incidence of these mutations in our cohort reflects the high cultural diversity in NSW, Australia (Australian Bureau of Statistics 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The p.R408W mutation was the predominant mutation in Ireland, Latvia and Lithuania (O'Donnell et al 2002;Kasnauskiene et al 2003;Pronina et al 2003), whereas c.1315+1G>A had the highest frequency in England, Germany and Denmark (Guldberg et al 1993;Aulehla-Scholz and Heilbronner 2003;Zschocke 2003). Other examples of region-specific mutations include c.1066-11G>A from Mediterranean regions and p.R243Q and p.R413P from Asia (Chien et al 2004;Lee et al 2004;Song et al 2005). The low incidence of these mutations in our cohort reflects the high cultural diversity in NSW, Australia (Australian Bureau of Statistics 2012).…”
Section: Discussionmentioning
confidence: 99%
“…1 Mass screening of newborns for PKU is performed in developed countries and patients show a wide spectrum of clinical severity. The incidence of PKU in Japan is 1/120 000, 2 which is lower than in Caucasians (1/10 000), 3 Chinese (1/18 000) 4 and Korean (1/41 000) 5 populations. The diagnosis of PKU is based on high phenylalanine levels and absence of tetrahydrobiopterin (BH 4 ) deficiency, rather than on hepatic PAH activity.…”
Section: Introductionmentioning
confidence: 94%
“…The distribution and frequency of PKU mutations were compared among Northern Chinese, 33 Korean, 5 Taiwanese 34 and Japanese populations. Figure 2 shows PKU mutations with 45% frequency in at least one of these countries.…”
Section: Comparison Among East Asian Countriesmentioning
confidence: 99%
“…In a previous study, only 86% of the mutant alleles were identified by sequence analysis of the entire PAH coding region, suggesting that large deletions or duplication are frequent causes of PKU in Koreans (Lee et al, 2004). To elucidate this hypothesis, we performed both sequencing and gene dosage analyses of the PAH gene in 33 unrelated Korean PKU patients.…”
Section: Introductionmentioning
confidence: 96%